A systematic review on the impact of breastfeeding on cancer risk, weight loss, cardiovascular disease, type 2 diabetes mellitus in mothers, and the role of fathers, medical personnel and training in breastfeeding - Krupa, Olga; Rybak, Daria; Kamińska-Omasta, Katarzyna; Omasta, Bartosz; Romańczuk, Kuba Borys; Czerska, Magdalena Agata; Pietrukaniec , Paulina Dorota; Stolarczyk, Szymon Przemysław; Wójcik, Zofia Martyna; Furtak, Kinga (Quality in Sport, 2025)
Introduction Breastfeeding has a significant impact on maternal health, in the long term it reduces the risk of certain cancers, cardiovascular diseases, type II diabetes, supports the process of weight loss after pregnancy and the formation of a strong bond between mother and child. In order to increase effectiveness among breastfeeding women, it is extremely important to educate them, as well as help from fathers and medical staff. Aim of the study Assessing the impact of breastfeeding on the risk of cancer, cardiovascular disease, type 2 diabetes In the mother and the role of fathers, medical personnel and training in the breastfeeding process Materials and Methods A review of the literature collected in the PubMed database was conducted to gather information under the headings: "breastfeeding and cancer," "health benefits for breastfeeding mothers," "breastfeeding and cardiovascular disease risk reduction," "impact of breastfeeding on type II diabetes risk," "role of fathers in breastfeeding," "role of medical personnel in breastfeeding," and "strategies affecting breastfeeding." Summary The review discusses the benefits of breastfeeding for mothers, such as reducing the risk of breast, ovarian and endometrial cancer, cardiovascular disease, and type 2 diabetes. It highlights the relationship between the timing of breastfeeding and the onset of specific conditions, as well as the role of fathers and health care providers in the breastfeeding process. The available data allow us to conclude that breastfeeding is an effective preventive health strategy, but further research is needed to understand the biological mechanisms and identify optimal supportive interventions.